HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN MINUM OBAT PADA PASIEN HIPERTENSI DI PUSKESMAS MANAHAN SURAKARTA - Widodo, Arvia Wahyu; Pambudi, Risma Sakti; Ahwan, Ahwan (Jurnal Farmasi & Sains Indonesia, 2023)
Hypertension is an increase in systolic blood pressure more than equal to 140 mmHg and diastolic more than equal to 90 mmHg. Good knowledge must be possessed by people with hypertension in order to better understand the importance of routine blood pressure control and to know the dangers caused if they do not take medication regularly. Compliance with taking antihypertensive medication is very important to increase the effectiveness of treatment and prevent complications. This study aims to determine the relationship between the level of knowledge and medication adherence in hypertensive patients at the Manahan Surakarta Health Center. The method used is an analytic observational method with a cross sectional approach. The instruments used in this study were the HK-LS (Hypertension Knowledge-Level Scale) questionnaire and the MMAS-8 (Morisky Medication Adherence) questionnaire to obtain primary data. Data collection was conducted in March 2023 with a sample size of 100 hypertensive patients. Knowledge of hypertension is low knowledge of 8%, moderate knowledge of 23% and high knowledge of 69%. The results of the presentation of medication adherence are low adherence of 16%, moderate adherence of 29%, high adherence of 55%. Based on bivariate analysis using Spearman's rank analysis a correlation coefficient of 0.571 was obtained with a p value of 0.000 <0.05 which means that Ho was rejected and Ha was accepted, that is, there was a significant relationship between knowledge about hypertension and adherence to taking medication in hypertensive patients at the Manahan Surakarta Health Center.